Chemistry - Blackman, Allan; Bottle, Steven; Schmid, Siegbert; Mocerino, Mauro; Wille, Uta (Milton, Qld, Australia : John Wiley & Sons Australia, Ltd., 2019)
Chemistry, science, stoichiometry, thermodynamics, organic chemistry
Intro; Chemistry; Brief contents; Contents; About the authors; 1 The atom; 1.1 The essential concepts in brief; 1.2 The atomic theory; 1.3 The structure of the atom; Atomic mass; 1.4 The periodic table of the elements; The modern periodic table; Naming the elements; 1.5 Electrons in atoms; SUMMARY; KEY CONCEPTS AND EQUATIONS; KEY TERMS; REVIEW QUESTIONS; REVIEW PROBLEMS; ADDITIONAL EXERCISES; ACKNOWLEDGEMENTS; 2 The language of chemistry; 2.1 Measurement; SI units; Non-SI units; Dimensional analysis; Precision and accuracy; Uncertainties and significant figures; 2.2 Representations of molecules and reactions Chemical formulae; Structural formulae; Three-dimensional structures; Mechanistic arrows in chemical reactions; 2.3 Nomenclature; Naming inorganic compounds; Naming organic compounds; SUMMARY; KEY CONCEPTS AND EQUATIONS; KEY TERMS; REVIEW QUESTIONS; REVIEW PROBLEMS; ADDITIONAL EXERCISES; MATHS FOR CHEMISTRY; The equation to be rearranged involves addition or subtraction; The equation to be rearranged involves multiplication or division; ACKNOWLEDGEMENTS; 3 Chemical reactions and stoichiometry; 3.1 Chemical equations; Specifying states of matter; 3.2 Balancing chemical equations3.3 The mole; 3.4 Empirical formulae; Mole ratios from chemical formulae; Determination of chemical formulae; Determination of empirical formulae; 3.5 Stoichiometry, limiting reagents and percentage yield; Mole ratios in chemical reactions; Limiting reagents; Percentage yield; 3.6 Solution stoichiometry; The concentration of solutions; Applications of solution stoichiometry; Stoichiometry of solutions containing ions; SUMMARY; KEY CONCEPTS AND EQUATIONS; KEY TERMS; REVIEW QUESTIONS; REVIEW PROBLEMS; ADDITIONAL EXERCISES; ACKNOWLEDGEMENTS; 4 Atomic energy levels; 4.1 Characteristics of atoms4.2 Characteristics of light; Wave-like properties of light; Particle properties of light; Absorption and emission spectra; Atomic spectra; Quantisation of energy; Energy level diagrams; 4.3 Properties of electrons; The Heisenberg uncertainty principle; 4.4 Quantisation and quantum numbers; Principal quantum number (n); Azimuthal quantum number (l); Magnetic quantum number (ml); Spin quantum number (ms); The Pauli exclusion principle; 4.5 Atomic orbital electron distributions and energies; Orbital electron distributions; Orbital energies; 4.6 Structure of the periodic table The Aufbau principle and order of orbital filling; Valence electrons; 4.7 Electron configurations; Electron-electron repulsion; Orbitals with nearly equal energies; Configurations of ions; Magnetic properties of atoms; Excited states; 4.8 Periodicity of atomic properties; Atomic radii; Ionisation energy; Electron affinity; Sizes of ions; 4.9 Ions and chemical periodicity; Cation stability; Anion stability; Metals, nonmetals and metalloids; s-block elements; p-block elements; SUMMARY; KEY CONCEPTS AND EQUATIONS; KEY TERMS; REVIEW QUESTIONS; REVIEW PROBLEMS
Includes index
CAS
Text in English
Keywords: Chemistry